Should multiple factor dilutions be performed for all patient coagulation factor assays? Let the debate begin! - Emmanuel J. Favaloro; Leonardo Pasalic (Research and Practice in Thrombosis and Haemostasis, 2022)
Abstract Laboratory assessment of blood coagulation factors may be undertaken for various reasons, including investigating the possibility of hemophilia or unexpected prolongation in routine coagulation assays (eg, prothrombin time, activated partial thromboplastin time). Several guidelines recommend performing multiple dilutions (usually 2‐3) on all patient test samples to evaluate “parallelism” as a guide to the presence of potential “inhibitors,” be they factor inhibitors, lupus anticoagulant, or related to the presence of anticoagulant therapy. The current Forum argues against mandating investigation of parallelism (or multiple dilutions) for all samples destined for testing, instead suggesting that a more targeted approach will likely provide better clinical utility and use of laboratory resources.